2001
DOI: 10.1007/pl00001838
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between selected monoterpene hydrocarbons in the xylem of six Pinus (Pinaceae) species

Abstract: The compositions of 23 monoterpene hydrocarbons of six pine species (Pinus syl6estris, P. yunnanensis, P. armandii, P. tropicalis, P. cubensis and P. caribaea) were compared, using multivariate data analysis. Four of the six species were clearly different from the other species in a Principal Components Analysis (PCA) model, based on the relative amounts (selective normalization) of the monoterpenes. The correlation coefficients between constituents were determined separately for each species and the strongest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
2
20
1
Order By: Relevance
“…There are also many low or moderate negative correlations between monoterpenes and diterpenes (data not shown). Strong correlations between two monoterpenes, α-pinene and camphene, were also found by Sjödin et al (2000) in Norway Spruce and Fäldt et al (2001) in six Pinus species (not including P. halepensis). Hiltunen and Laakso (1995) and Wise and Croteau (1999) suggested that these strong correlations might indicate a common precursor.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…There are also many low or moderate negative correlations between monoterpenes and diterpenes (data not shown). Strong correlations between two monoterpenes, α-pinene and camphene, were also found by Sjödin et al (2000) in Norway Spruce and Fäldt et al (2001) in six Pinus species (not including P. halepensis). Hiltunen and Laakso (1995) and Wise and Croteau (1999) suggested that these strong correlations might indicate a common precursor.…”
Section: Discussionsupporting
confidence: 51%
“…Hiltunen and Laakso (1995) and Wise and Croteau (1999) suggested that these strong correlations might indicate a common precursor. On the other hand, Fäldt et al (2001) reported a strong correlation between α-and β-pinene which was not found in the present analysis of P. halepensis.…”
Section: Discussioncontrasting
confidence: 45%
“…However, previous enantiomeric analyses of individual tree xylem have shown highly variable enantiomeric ratios from 90% (−)-α-pinene to 80% (+)-α-pinene, even from different parts of the same tree (Norin, 1996;Fäldt et al, 2001). In contrast, the spatially and temporally more extensive ecosystem scale data presented here shows a clear enantiomeric predominance in ambient air, so what could be the underlying reason for the clear dominance of the (+)-form of α-pinene over the Boreal forest and the (−)-form in air over the rainforest?…”
Section: Discussionmentioning
confidence: 97%
“…Among the most important volatile compounds emitted from boreal coniferous forests are monoterpenes and sesquiterpenes, which form a major proportion of the conifer oleoresin (Fäldt et al, 2001) and contribute to the constitutive emissions from trunks, needles and roots. The oleoresin is formed in e.g.…”
Section: Introductionmentioning
confidence: 99%